Reasons to Reason in Primary Maths and Science - Borthwick, Alison (SAGE Publications, 2018)
This book explores what reasoning is and what it is not. It includes background theory and a rationale for primary teachers alongside examples of how reasoning in primary mathematics and science classes can develop.